La prévention juridique - Roussin, Claude (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1980)
In recent years, the practice of law has come under renewed criticism as to the objectives it pursues. Out of this debate grew the concept of preventive law. This paper seeks to explain the meaning of preventive law and demonstrate its relevance for the legal system of Québec, by outlining its main features, its peculiar methods and a strategy for its implementation. Preventive law can be most clearly distinguished from the traditional practice of law by a shift in priorities away from litigation to the maximization of certainty as to one's rights and duties. This new approach involves reform-mindedness, sensitivity to the citizen's needs and an offensive rather than defensive outlook. The typical preventive-law method is the annual check-up of the citizen's « legal health ». This requires the devising of checklists through which the safety of legal transactions may be ascertained. Other preventive-law methods include standard contract forms and legal self-aid kits. The implementation of a preventive-law approach should involve three centres of responsibility. The lawyer's office would of course remain the major stage on which the practice of law is carried out. But the focal point for initiating and developing preventive-law methods must be located elsewhere. In the Quebec context, the Société québécoise d'information juridique, being already active in the field of legal information, seems naturally suited to the task. In the short term, however, law schools must provide the initial impetus towards a policy of legal prevention.